Conceptual frameworks in didactics – learning and teaching: Trends, evolutions and comparative challenges. (January 2018) - Ligozat, Florence; Almqvist, Jonas
This special issue of the European Educational Research Journal presents a series of research papers reflecting the trends and evolutions in conceptual frameworks that took place within the EERA 27 'Didactics – Learning and Teaching' network during its first ten years of existence. Most conceptual tools used in this field were elaborated in different socio-historical contexts for education and schooling delineated by nations and/or linguistic regions in Europe. This issue suggests possible integrative paths between certain frameworks debated in the Network 27 through co-authored papers. Crossed perspectives on the papers highlight certain important foci in the study of learning and teaching processes: (i) 'Bildung' discussed within didactics as a European research field; (ii) Educational goals, content and teaching methods expressed in curricula; (iii) Curriculum making processes; (iv) Teaching qualities, teaching (joint) actions and classroom discourses; and (v) Collaborative practices in teacher professional development. Finally, two strands of comparative research in didactics are sketched for increasing synergies in the field.